Tanggung Jawab Pemilik Konten yang Mengunggah Ulang Video di Jejaring Media Sosial Menggunakan Prinsip Penggunaan Wajar menurut Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - muhammad Ifqie Dzikrullah; Efridani Lubis; Fauziah Fauziah (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2021)
This thesis discusses the responsibility of content owners who re-upload videos on social media networks. This thesis is motivated by the large number of re-uploaders making content creators nervous because a content creator has made a video with great effort. Many YouTubers have appealed to